Evaluation of a reversibly immortalized human hepatocyte line in bioartificial liver in pigs - Lifu Zhao , Jianzhou Li , Guoliang Lv , Anye Zhang , Pengcheng Zhou , Ying Yang; Xiaoping Pan , Xiaopeng Yu , Yimin Zhang , Shusen Zheng, Yu Chen , Yuemei Chen; Chengbo Yu , Weibo Du , Tao Song , Jiansheng Xu , Yang Yu , Lanjuan Li (African Journal of Pig Farming, 2019)
An appropriate cell source is essential for the clinical application of bioartificial liver (BAL) system. This study aimed to test a reversibly immortalized human hepatocyte line (HepLi-4) in our newly validated choanoid fluidized bed bioreactor based BAL in pigs with fulminant hepatic failure (FHF). 15 FHF pigs were allocated to three groups: a BAL group receiving BAL treatment with HepLi-4 cells; a sham BAL group receiving cell-free BAL treatment; and a FHF group receiving intensive care only. Expression of liver-specific genes in HepLi-4 cells before and after BAL was analyzed, adult human hepatocytes acted as a reference. In BAL group, Fischer index was higher and serum indirect bilirubin level was lower compared with two control groups. Survival time in BAL group was longer than that in two control groups, but the difference was not statistically significant. Gene expression analysis showed that the transcript levels of liver-specific genes in HepLi-4 were retained after BAL, but significant variations were observed between HepLi-4 and human hepatocytes. HepLi-4 showed beneficial metabolic effects on FHF pigs in BAL, but is still not an appropriate cell source for BAL. More insights into interpreting the conditions for hepatocyte differentiation are needed.v